2013
DOI: 10.1128/mcb.00278-13
|View full text |Cite|
|
Sign up to set email alerts
|

Lack of tRNA Modification Isopentenyl-A37 Alters mRNA Decoding and Causes Metabolic Deficiencies in Fission Yeast

Abstract: d tRNA isopentenyltransferases (Tit1) modify tRNA position 37, adjacent to the anticodon, to N 6 -isopentenyladenosine (i6A37) in all cells, yet the tRNA subsets selected for modification vary among species, and their relevance to phenotypes is unknown. We examined the function of i6A37 in Schizosaccharomyces pombe tit1؉ and tit1-⌬ cells by using a ␤-galactosidase codon-swap reporter whose catalytic activity is sensitive to accurate decoding of codon 503. i6A37 increased the activity of tRNA Cys at a cognate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
121
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(133 citation statements)
references
References 73 publications
12
121
0
Order By: Relevance
“…The PHA6 northern blot assay is based on a DNA probe complementary to the anticodon loop which hybridizes better in the absence of i6A37 and a probe complementary to a different region of the same tRNA as a quantitative internal control. The procedure can be used to calibrate and measure differences in i6A37 modification (Lamichhane et al 2011(Lamichhane et al , 2013a(Lamichhane et al , b, 2016Yarham et al 2014).…”
Section: The State Of the Trna Population In The Cellmentioning
confidence: 99%
“…The PHA6 northern blot assay is based on a DNA probe complementary to the anticodon loop which hybridizes better in the absence of i6A37 and a probe complementary to a different region of the same tRNA as a quantitative internal control. The procedure can be used to calibrate and measure differences in i6A37 modification (Lamichhane et al 2011(Lamichhane et al , 2013a(Lamichhane et al , b, 2016Yarham et al 2014).…”
Section: The State Of the Trna Population In The Cellmentioning
confidence: 99%
“…Deletion of the IPTase decreases sup-tRNA activity in fission (tRNA Ser ) and budding yeast (tRNA Tyr ) causing loss of TMS phenotype (Laten et al 1978;Janner et al 1980;Laten 1984;Dihanich et al 1987; see Kohli et al 1989) with no effect on the levels of the sup-tRNA (Lamichhane et al 2013a). Another phenotype of S. pombe tit1-Δ is sensitivity to rapamycin, an inhibitor of TOR kinase (Lamichhane et al 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Schizosaccharomyces pombe has five i6A37-cy-tRNAs, comprised of three cy- (Chan and Lowe 2009;Lamichhane et al 2011). An assay in S. pombe dependent on decoding of a Tyr codon in the active center of β-galactosidase revealed that loss of i6A37 decreased cy-tRNA Tyr specific activity by approximately threefold (Lamichhane et al 2013a). A more facile and widely used assay is tRNA-mediated suppression (TMS) in which the activity of a suppressor-tRNA (suptRNA) to decode/suppress a premature stop codon in a reporter mRNA encoding a metabolic enzyme in an adenine synthetic pathway is monitored by red-white colony color (for review, see Rijal et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations